Functional and association studies of the cholesteryl ester transfer protein (CETP) gene in a Wannan Black pig model. (18th October 2015) - Ding, Y. Y.; Zhang, W.; Zhang, M. Q.; Fu, K.; Chen, W. P.; Ding, C.; He, X. L.; Zhang, X. D.; Huang, L.; Yin, Z. J.
Summary: Some polymorphisms of the human CETP gene are causally and significantly associated with serum lipids levels; however, the information regarding this gene in pigs is sparse. To evaluate the effects of CETP on blood lipid traits and fat deposition in pig, porcine CETP tissue expression patterns were observed by quantitative real‐time polymerase chain reaction (qPCR) first. High expression was detected in liver, spleen, gluteus medius (GM) muscle and backfat. A de novo polymorphism (AF333037:g.795C>T) in the intron 1 region of porcine CETP was identified. This polymorphism was further genotyped by direct sequencing of the PCR products of 390 Wannan Black pigs, a Chinese native breed population. Association analyses at 45 and 300 days of age revealed highly significant associations between CETP genotypes and serum lipid traits. Furthermore, this polymorphism was proved to be associated with differences in liver CETP mRNA levels: pigs at 300 days of age with the TT genotype had higher levels than did those with other genotypes ( P =  0.021). Additionally, analysis at 300 days of age showed that GM CETP mRNA expression correlated positively with serum lipids levels as well as with carcass backfat thickness and intramuscular fat content in GM. These results indicate that CETP is involved in serum, adipose and muscle lipid metabolism in pigs. The mechanisms underlying such relationships and their functional implications are worthy of further research.